Phylogeographical Evolution & Genetic Structure of Populations of Sitophilus zeamais (Coleoptera, Curculionidae), Pests of Stocked Corn in West Africa - (:unkn) unknown (My University, 2018)
The maize weevil or Sitophilus zeamais (Motschulsky, 1855) is known because of its extraordinary potential for destroying stored grain; but little is known about its phylogeography and genetic structure in sub-saharan Africa. Therefore, the aim of this thesis is to define the phylogeography of West African populations and to estimate their gene flow using sequencing data (Cytochrome B and Cytochrome oxidase I) and genotyping. The analysis of the latter reveals the presence of 30 haplotypes (mtDNA) against 33 alleles (SSR). The majority haplotype represented about 43% of the total population and connected West Africa to Central Africa. Molecular analyzes indicated the presence of a genetic structure without a phylogeographic signal. This is the result of an asymmetric multidirectional flow (cross infestation) that would most likely be related to anthropogenic impacts through commercial activities. Populations also showed good viability potential reinforced by passive dispersal through the grain trade; and genetic diversity is more important in the north from which dispersal routes would have started since the Pleistocene period. The multivariate and Bayesian inferences suggested the existence of 4 to 5 main clusters that have separated after a bottleneck followed by a moderate population expansion since the Pleistocene period.This study provided new insights into the description of the genetic basis and differentiation of S. zeamais populations in the West African sub-region. It also helped to understand the processes that govern the biogenetic parameters of these populations. Therefore, it constitutes prospects for sustainable management of resources. Indeed, knowledge of evolutionary biology can influence parameters to reduce or even eliminate harmful effects of these pests.
Keywords: African Research